Intelligent site selection for bricks-and-mortar stores. (28th August 2019) - Ge, Dongdong; Hu, Luhui; Jiang, Bo; Su, Guangjun; Wu, Xiaole
Abstract : Purpose: The purpose of this paper is to achieve intelligent superstore site selection. Yonghui Superstores partnered with Cardinal Operations to incorporate a tremendous amount of site-related information (e.g. points of interest, population density and features, distribution of competitors, transportation, commercial ecosystem, existing own-store network) into its store site optimization. Design/methodology/approach: This paper showcases the integration of regression, optimization and machine learning approaches in site selection, which has proven practical and effective. Findings: The result was the development of the "Yonghui Intelligent Site Selection System" that includes three modules: business district scoring, intelligent site engine and precision sales forecasting. The application of this system helps to significantly reduce the labor force required to visit and investigate all potential sites, circumvent the pitfalls associated with possibly biased experience or intuition-based decision making and achieve the same population coverage as competitors while needing only half the number of stores as its competitors. Originality/value: To our knowledge, this project is among the first to integrate regression, optimization and machine learning approaches in site selection. There is innovation in optimization techniques.